Daniel Forthomme, l’optométriste, le professeur, le chercheur, le directeur et l’ami (1938-2019) - Giasson, Claude; Gresset, Jacques; Simonet, Pierre (Canadian Journal of Optometry, 2020)
Our friend, Daniel Forthomme, passed away last November 25. This text, dedicated to his memory, list his numerous contributions to optometrists and optometry. Notre ami, Daniel Forthomme, est décédé le 25 novembre dernier. Ce texte, dédié à sa mémoire, énumère ses nombreuses contributions aux optométristes et à l’optométrie.